Keeping it Clean: Pest Control, Roaches and Ants - Mary N. Harrison (EDIS)
The two most common insects that present pest control problems for Floridians are roaches and ants. This document is FCS5232-12, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised November 2005.